Political connections, political corruption and auditing: a literature review. Issue 1 (10th June 2021) - Khelil, Imen; Khlif, Hichem; Amara, Ines
Abstract : Purpose: Given the interest in better understanding the economic effects of political connections and political corruption on auditor behavior, this paper aims to review empirical studies in the accounting and finance domain dealing with these topics. Design/methodology/approach: Keywords used to search for relevant studies include "political connections or political corruption" with "audit fees, audit report lag, audit independence and audit opinion." This paper consults several editorial sources including Elsevier, Electronic Journals Service Elton B. Stephens Company, Emerald, Springer, Palgrave Macmillan, Sage, Taylor and Francis and Wiley-Blackwell. The search yields 16 published studies since 2006. Findings: The review reveals that the majority of studies dealing with the economic effect of political connections are conducted in an Asian setting. Political connections increase the likelihood of receiving a favorable audit opinion and they are associated with higher audit fees longer audit delays. However, they can compromise auditor independence. Studies dealing with the economic consequences of political corruption on auditing are mostly based in the US setting. The findings of the reviewed studies suggest that political corruption is associated with higher audit fees, longer audit delays and increases the likelihood of receiving a going concern audit opinion. Practical implications: The synthesis suggests that political connections can adversely (compromise auditor independence) or beneficially (reduce the likelihood of issuing a going concern audit opinion) impact auditor behavior depending on the legal, institutional and cultural characteristics prevailing in a particular setting. Political corruptions increase audit assessed risks leading to a higher probability of issuing a going concern audit opinion and increased audit effort (audit fees and audit delays). It should be noted here that the literature linked to political corruption and auditor behavior is still in its infancy and much remains to be learnt if this stream of research is examined outside the US setting. Originality/value: The review discusses the political connections and political corruption literature specifically devoted to auditor behavior. It identifies some limitations of this literature and offers guidance for future research avenues.